Correlation and path analysis in turmeric (Curcuma longa L.) - Chattapadhyay, B Panja, D K De, B Basak, S B (Journal of Spices and Aromatic Crops, 2002)
Studies on nineteen characters of eight turmeric (Curcuma longa L.) genotyoes revealed that plant height, leaf number, number of primary fingers, number and weight of secondary fingers had positive genotypic correlation while length of primary fingers, internode length and ratio of outer and inner core of primary fingers had significant negative association with rhizome yield. The number and weight of secondary rhizomes exhibited higher positive correlation with yield than other characters. Path analysis indicated higher direct positive effect of weight of primary and mother rhizomes but insignificant correlation with rhizome yield due to higher indirect negative effect of some of the component characters. On the contrary, the number of primary fingers had the highest direct negative effect on rhizome yield, but significantly positive correlation with it, apparently due to high positive indirect effect via weight of primary and mother rhizomes and number of secondary rhizomes. The importance of plant height, leaf number, number of primary fingers, number and weight of secondary fingers as criteria for selection of bitter turmeric genotypes has been indicated.